1996
DOI: 10.1002/(sici)1097-0304(199604)37:4<382::aid-ccd8>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Lesion-directed administration of alteplase with intracoronary heparin in patients with unstable angina and coronary thrombus undergoing angioplasty

Abstract: Percutaneous coronary revascularization in patients with unstable angina and coronary thrombus carries a high complication rate. A new strategy to reduce thrombus burden before revascularization was tested in a multicenter prospective trial. Patients with unstable angina and coronary thrombus (n = 45) received alteplase through an infusion catheter at the proximal aspect of the target lesion and concomitant intracoronary heparin via a standard guiding catheter. Angiography was performed before and after lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…For instance, intracoronary t-PA registry investigators found significant improvements in the coronary TIMI flow grade and thrombus dissolution with intracoronary t-PA in 198 patients (206 cases) 9) . Gurbel PA et al found that lesion-directed delivery of alteplase resulted in more prolonged local thrombolysis and thrombus score reduction in 45 unstable angina patients with coronary thrombus 10) . Recently, Kelly RV et al reported that the administration of intracoronary thrombolytics (tenecteplase) in complex PCI after the onset of thrombotic complications is safe and may even improve the success rate in PCI complicated by thrombus in the study of 34 patients (22 with acute ST elevation MI, 4 with rescue PCI, 6 with non-ST elevation MI, and 2 during elective PCI) 11) .…”
Section: A B Cmentioning
confidence: 99%
“…For instance, intracoronary t-PA registry investigators found significant improvements in the coronary TIMI flow grade and thrombus dissolution with intracoronary t-PA in 198 patients (206 cases) 9) . Gurbel PA et al found that lesion-directed delivery of alteplase resulted in more prolonged local thrombolysis and thrombus score reduction in 45 unstable angina patients with coronary thrombus 10) . Recently, Kelly RV et al reported that the administration of intracoronary thrombolytics (tenecteplase) in complex PCI after the onset of thrombotic complications is safe and may even improve the success rate in PCI complicated by thrombus in the study of 34 patients (22 with acute ST elevation MI, 4 with rescue PCI, 6 with non-ST elevation MI, and 2 during elective PCI) 11) .…”
Section: A B Cmentioning
confidence: 99%
“…1. Study protocol performed blindly by two experienced interventional cardiologists to record a thrombotic score as followings: 0, no thrombus; 1, intraluminal haziness; 2, definite thrombus with its diameter or length < 0.5 times normal vessel diameter; 3, 0.5-2 times; 4, > 2 times (Gurbel et al 1996). Angiographic overt thrombosis was defined as having thrombotic scores of 3-4.…”
Section: Abdominal Aorta Angiographymentioning
confidence: 99%
“…Angiographic data: Coronary angiography and subsequent needed intervention for the culprit vessel was done for each patient according to the index time of each study group with the following data obtained: Culprit and other vessel affection, site of the lesion, type of the lesion according to AHA/ACC classification system into 3 types A, B and C, [12] the degree of stenosis, thrombus burden, [13] TIMI flow, [14] and myocardial blush grade (MBG) [15] were assessed. N.B.…”
Section: Ecgmentioning
confidence: 99%